Rice straw biochar and different rates of urea on rice yield, CH4 and CO2 gases emission - Lai, Lai; Ismail, Mohd Razi; Mohammad Yusoff, Martini; Ismail, Roslan (Instituto de Investigaciones Agropecuarias, 2021)
The application of biochar using inorganic fertilizer has been reported as being more efficient for the effective growth of soil microbes. However, there is no evidence that rice straw biochar (9 t ha-1) and different urea rates have had any effect on greenhouse gas (GHG) emissions of rice (Oryza sativa L.) production in tropical soils. Therefore, this study was conducted to investigate the effects of urea and the application of rice straw biochar (9 t ha-1) on yield and GHG emissions. Treatments were 150 kg N ha-1 (T1 control) and rice straw biochar (9 t ha-1) combined with 30, 60, 90, 120, and 150 kg N ha-1 (T2, T3, T4, T5, and T6, respectively). The experiment had a randomized complete block design with four replicates. Grain yield increased 20.7% in plants grown in T3, T4, and T5 compared with the control. Although all biochar treatments had increased cumulative CO2-C emissions compared with the control (5.0% to 7.6%), the cumulative CH4 emissions significantly decreased compared with the control (20% to 27%). Therefore, it could be suggested that T3 and T4 (9 t ha-1 rice straw biochar with 60 and 90 kg N ha-1) increase yield and reduce CH4 emissions relative to the control. Although this study was limited to a pot experiment with no nutrient leaching, the synergetic effect of rice straw biochar (9 t ha-1) and reduced urea rate is worth mentioning for acidic paddy soil; a field experiment is suggested to determine the long-term effect of biochar.